Aplikasi Beberapa Hasil Fermentasi Limbah terhadap Pertumbuhan Bibit Kopi Robusta (Coffea canephora Pierre) - Suhendra, Iwan; Armaini, Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aim to know which the waste has the big effect to increase the growth of coffee Robusta seedlings. The experiment has been conducted at the Experimental Farm of the Faculty of Agriculture. The experimental unit was arranged in a Completely Randomized Design with 6 treatments of waste fermentation ie without waste (L0), LCPKS (L1), tofu waste (L2), cow urine (L3), waste of reeds (L4), Banana skin waste (L5).Parameters observed were height increment (cm), number of leafesincrement, increase of stem diameter (cm), leaf area (cm2), dry weight of plant (g), and root canopy ratio. Data were analyzed using analysis of variance and the mean of each treatment was compared with Test of Honest Real Difference at 5% level.The results showed that the treatment of fermentation of tofuwaste gave a best effect in increasing the growth of robusta coffee seeds aged 3-6 months.. Keywords : coffee seedling, LCPKS, Tofu waste, Cow urine , waste of reeds, banana skin waste.